1988
DOI: 10.1021/bi00417a041
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-protein interactions mediate the photochemical function of rhodopsin

Abstract: We have investigated the molecular features of recombinant membranes that are necessary for the photochemical function of rhodopsin. The magnitude of the metarhodopsin I to metarhodopsin II phototransient following a 25% +/- 3% bleaching flash was used as a criterion of photochemical activity at 28 degrees C and pH 7.0. Nativelike activity of rhodopsin can be reconstituted with an extract of total lipids from rod outer segment membranes, demonstrating that the protein is minimally perturbed by the reconstituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
206
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(218 citation statements)
references
References 42 publications
11
206
1
Order By: Relevance
“…The resulting signals correspond to the 'a' and 'b' waves of the electroretinogram. Membrane fatty acid composition affects the ability of photons to transform rhodopsin to the activated state (Weidmann et al 1988;Mitchell et al 1992). The rhodopsin activation in response to light involves a transformation of the metarhodopsin I form to the metarhodopsin II form.…”
Section: Essential Fatty Acid Supply Affects Lipid Membrane Structurementioning
confidence: 99%
“…The resulting signals correspond to the 'a' and 'b' waves of the electroretinogram. Membrane fatty acid composition affects the ability of photons to transform rhodopsin to the activated state (Weidmann et al 1988;Mitchell et al 1992). The rhodopsin activation in response to light involves a transformation of the metarhodopsin I form to the metarhodopsin II form.…”
Section: Essential Fatty Acid Supply Affects Lipid Membrane Structurementioning
confidence: 99%
“…For MAS NMR spectroscopy experiments, the labeled rhodopsin was concentrated and reconstituted into dioleolyl phosphatidylcholine vesicles by octyl-␤-D-glucoside dialysis in the presence of the phospholipid at a 300:1 molar ratio of lipid to protein (24)(25)(26). The extent of reconstitution was determined by UV͞Vis spectroscopy on samples resolubilized with detergent.…”
Section: Large-scale Expression Of Isotope-labeled Rhodopsinmentioning
confidence: 99%
“…In earlier reconstitution experiments with bovine rhodopsin it was established that the equilibrium concentration of Meta-II rhodopsin increased with the concentration of DHA hydrocarbon chains in the lipid matrix (5)(6)(7). Also the headgroups of phospholipids had a significant effect on Meta-II formation (5,7) and activation of G t (8,9).…”
mentioning
confidence: 98%
“…Also the headgroups of phospholipids had a significant effect on Meta-II formation (5,7) and activation of G t (8,9). It was observed that phosphatidylethanolamines (PE) and the negatively charged phosphatidylserines (PS) increased the amount of Meta-II.…”
mentioning
confidence: 99%